Advanced parametrisation of phase change materials through kinetic approach. (15th December 2021) - Lizana, Jesus; Perejón, Antonio; Sanchez-Jimenez, Pedro E.; Perez-Maqueda, Luis A.
Highlights: Thermal and kinetic experimental characterisation of PEG1500. Parametrisation of phase change process using the kinetic approach. Comparison with conventional kinetic-independent phase transition models. Higher accuracy of the kinetic approach to correctly simulate phase change. High influence in heat transfer when different heat exchange rates are involved. Abstract: Phase change materials (PCM) have been widely investigated for heat storage and transfer applications. Numerous numerical simulation approaches have been proposed for modelling their behaviour and predicting their performance in thermal applications. However, simulation approaches do not consider the kinetics of the phase transition processes, compromising the accuracy of their predictions. The phase change is a kinetically driven process in which both the reaction rate and the reaction progress depend on the heating schedule. This work evaluates and parametrises the influence of kinetics in the melting and crystallisation behaviour of a well-known PCM, PEG1500, and compares potential discrepancies with common phase change parametrisation alternatives. The kinetic dependence was experimentally evaluated through differential scanning calorimetry (DSC). The kinetic parameters required for modelling the kinetics of the processes were determined by both model-free and model-fitting procedures following ICTAC (International Confederation for Thermal Analysis and Calorimetry) recommendations. Then, the phase transition was parametrised through a kinetic model and compared with three conventional phase transition models: linear without hysteresis, non-linear without hysteresis, and non-linear with hysteresis. The statistical comparison between models demonstrates the higher accuracy of the kinetic approach to correctly represent the partial enthalpy distribution of latent heat storage materials during alternative phase change rates, obtaining a coefficient of determination (R 2 ) of 0.80. On the other hand, the accuracy of kinetic-independent models is limited to the range from 0.40 to 0.61. The results highlight the high discrepancies of conventional models compared to the kinetic approach and provide criteria and guidelines for efficient kinetic modelling of phase change in heat transfer evaluations.